Edukasi Latihan Fisik Aktivitas Motorik Kasar untuk Mencegah Kelemahan Otot Lansia Penghuni Panti Werda: Physical Exercise Education on Gross Motor Activities to Prevent Muscle Deterioration of Elderly in Nursing Home - Gunawan, Shirly; Tadjudin, Noer Saelan; Yunita, Fenny; Pratama, Raka Yoga; Tanuhariono, Ardhita Felicia; Pandean, Felicia; Liemitang, Gregorius Edward; Sari, Dwita Linda (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Indonesia has entered an aging population structure where the percentage of the elderly population has reached more than 10% since 2021. According to WHO data, the elderly population in Indonesia was 9.92% in 2020 and will increase to 20% in 2045. One of the health problems faced by the elderly is muscle weakness. Community service activities are carried out to prevent this disorder from becoming more progressive. These activities, which aim to train several physical exercise movements for gross motor activities, have significantly improved muscle strength, balance, and overall physical health in older people. Education is delivered through video screenings, live demonstrations, and socialization through banner media. The physical exercises taught can be done individually or in groups through games. This PKM activity was attended by 61 residents of nursing homes, most of whom were in the 71-80 year age group (39.34%) and over 80 years (39.34%), with an average age of 77.98 years. All participants agreed that the PKM activities held were interesting and valuable. Most elderly are interested in participating in other physical exercise activities in the future (97.87%). And after participating in this educational activity, 70.21% of older people became more motivated to do it routinely. The type of gross motor activity physical exercise preferred by older people is individual physical exercise, namely, tiptoe exercises (72.34%), raising and lowering the ball (68.09%), and bending the legs backward (65.96%).